HARMONISASI SYARIAT ISLAM DI JORONG KOTO TUO DALAM PELAKSANAAN BIMBINGAN PRA-NIKAH YANG BERBASIS ADAT - Rizka Novita; Irma Suryani; Emrizal Emrizal; Amri Effendi (UIN Mahmud Yunus Batusangkar, 2022)
This study examines the rules of pre-marital guidance in Jorong Koto Tuo Nagari Salimpaung in terms of Maslahah Mursalah. This study uses field research. The problem is that there are rules issued by niniak mamak in jorong koto tuo which require their children to attend pre-marital guidance at the surau before registering their marriage with the KUA so that there are two pre-marital guidances. -Marriage for children and how is Maslaha Murslah's review of pre-marital guidance for children. This research is field research, the data were obtained through interviews, observation, and documentation, after the data was collected it was processed by reducing the data by focusing on the important things, then narrated descriptively and analyzed inductively. This study found that pre-marital guidance for children in Jorong Koto Tuo was carried out by providing customary provisions for the bride and groom, how to live in the community, and equipping them with religious knowledge as provisions for married life. Pre-marital guidance has a positive impact in the form of additional knowledge as a provision for participating in pre-marital counseling at KUA, helping KUA in forming a sakinah mawaddah warahmah family, easily adapting to the customs that exist in Jorong Koto Tuo, in addition to that, children who are men will be more appreciated by niniak mamak from the wife's family. In addition, there is a negative impact from pre-marital counseling in terms of the time span between the pre-marital counseling held by niniak mamak and marriage registration at the KUA. In terms of costs, the children who have to spend more on transportation costs to attend two pre-marital counseling sessions. Pre-marital guidance in the perspective of Islamic law is permissible because this pre-marital guidance contains benefits because the children receive mature provisions as provisions in household life. legally, the maslahah mursalah is greater than the harm, so this does not conflict with the maslahah mursalah.